Pro Java 7 NIO.2 - Leonard, Anghel (Apress, 2011)
Pro Java 7 NIO.2 addresses the three primary elements that offer new input/output (I/O) APIs in Java 7, giving you the skills to write robust, scalable Java applications: An extensive file I/O API system addresses feature requests that developers have sought since the inception of the JDK A socket channel API addresses multicasting, socket binding associated with channels, and related issues An asynchronous I/O API enables mapping to I/O facilities, completion ports, and various I/O event port mechanisms to enhance scalability NIO.2 for the Java platform, known as JSR 203, is a major feature of the new Java JDK 7 under the leadership of Alan Bateman as an OpenJDK project. Take advantage of these exciting new developments with Pro Java 7 NIO.2.